Development and Assessment of Topical Niosomal Gel of Non-Steroidal Anti-Inflammatory Drug - AMLAVDIYA, SUNIL AMLAVDIYA; PAGARE, APURVA; SONARTIA, SUNITA; PATIDAR, SUNITA (International Journal of Multidisciplinary Research and Studies, 2023)
The study aimed to develop and assess a topical Niosomal gel formulation of NSAIDs to enhance drug delivery, improve therapeutic efficacy, and reduce adverse effects. Niosomes, a vesicular carrier system, were used to encapsulate and deliver the NSAID topically, improving drug retention and penetration. The Niosomal gel was characterized by its particle size, zeta potential, drug entrapment efficiency, stability, and rheological properties. The in vitro release kinetics and skin permeation and retention studies were conducted using in vitro and ex vivo models. The results showed that the developed topical Niosomal gel formulation provided controlled drug release, enhanced skin permeation, and improved drug retention compared to conventional gels. These findings suggest the potential utility of Niosomal gel formulations for localized NSAID delivery, offering improved therapeutic outcomes while minimizing systemic side effects.